(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
Every Food Service Operation/Hotel requires material, suppliers, equipment etc. The challenge is to procure the materials of the right quality, in the right quantity, at the right time, at the right price, from the right source with delivery at the right place. Efficient purchasing will be reflected in the quality, reputation and sources of any Hotel/Food Service Operation. Good Food & Beverage Service beings with wise buying. Bad purchasing will result in loss of revenue and loss of goodwill for any organization including Food Service Operations. The GIGO factor (garbage in garbage out) can result in the downfall of any food & beverage business. Hence it is imperative that organization pay proper attention of the purchasing function and devote resources to resource to research and establish system in this area.